Encouraging Individual Contributions to Net-Zero Organizations: Effects of Behavioral Policy Interventions and Social Norms - Karola Bastini; Rudolf Kerschreiter; Maik Lachmann; Matthias Ziegler; Tim Sawert (Journal of Business Ethics, 2023)
To contribute to a better understanding of the determinants of climate-friendly organizational behavior, we study the potential of behavioral policy interventions and social norms to foster individual contributions to organizational decarbonization initiatives. We investigate the effects of different types of behavioral policy interventions (default nudges vs. short-term boosts) in isolation and when they are combined with normative appeals to adopt climate-friendly behaviors in an organizational context. In a 20.167em0.167em2 between-subjects experiment, we find that default nudges generally induced higher individual contributions to organizational carbon compensation programs than short-term boosts. Moreover, injunctive social norm information decreased the effectiveness of both types of behavioral interventions but affected the effectiveness of short-term boosts to a stronger extent than the effectiveness of default nudges. Contributing to the nascent literature on motivating climate change mitigating behaviors in organizational contexts, we additionally explore whether factors such as personality traits, pro-social and pro-environmental beliefs, attitudes, and behaviors, and the degree of organizational identification exert an influence on the effectiveness of the interventions and provide qualitative insights into participants' reasoning for their decisions.
Keywords: 300; Climate-friendly organizational behavior; Organizational policy interventions; Nudge; Boost; Social norm